Mapping Our School Site - Hagevik, Rita A. (Educar em Revista, 2011)
Mapping Our School Site (MOSS) is a program in which students practice spatial cognition skills by field mapping and analysis using Geographic Information Systems (GIS). Middle school students’ spatial ability was evaluated using a Spatial Experience Survey (SES) and the revised Purdue Spatial Visualization Test: Rotations (PSVT: R). other sources of data included interviews, group presentations, individual written conclusions, and mapping analyses. Students’ problem solving identification and ability dramatically improved as they collected, evaluated, reported, and synthesized environmental data. The MOSS program combined an out of doors experience with an indoor experience on the computer. This was found to be an effective approach to this type of field study.